Making America's Children Safe Again2: Advocating for CAPTA Reform and Beyond. (March 2017) - Harfeld, Amy; Marlowe, Kendall
Abstract : With government's response to child abuse and neglect seen as one of the most daunting challenges for public policy and law, legislative reform on this issue struggles to adequately protect children while preserving the integrity of family. The authors utilize the Child Abuse Prevention and Treatment Act (CAPTA) as an example of the funding and policy challenges in reforming federal child welfare law, as well as a lens through which advocates can locate both conventional and unconventional tools to move forward. CAPTA is examined as an important but weak and flawed federal statute. Authors present an array of opportunities to improve CAPTA during the next reauthorization cycle. Noting exemplary successes, in other recent and related legislation reforms, are suggested for CAPTA to more effectively address ongoing challenges of child welfare.